Use of telemedicine for opioid use disorder treatment – Perceptions and experiences of opioid use disorder clinicians. (1st November 2021) - Riedel, Lauren; Uscher-Pines, Lori; Mehrotra, Ateev; Busch, Alisa B.; Barnett, Michael L.; Raja, Pushpa; Huskamp, Haiden A.
Highlights: Surveyed clinicians used telemedicine for over half of visits for opioid use disorder in fall 2020, including a sizeable share via audio-only. Most clinicians found tele-OUD to be as effective as in-person and were more comfortable using video for clinically stable (vs unstable) patients. Post-pandemic, most clinicians prefer to use in-person care for the majority of visits but nearly all would like to offer telemedicine in some form. Abstract: Objective: To understand clinician use of and opinions about telemedicine for opioid use disorder (tele-OUD) during the COVID-19 pandemic. Methods: An electronic national survey was administered in fall 2020 to 602 OUD clinicians recruited from WebMD/Medscape's online panel. The survey completion rate was 97.3 %. Results: On average, clinicians reported that 56.9 % of their visits in the last month were via telemedicine (20.3 % via audio-only and 36.6 % via video). Most respondents (N = 376, 62.5 %) agreed that telemedicine has been as effective as in-person care. The majority (N = 535, 88.9 %) were comfortable using video for clinically stable patients, while half (N = 297, 49.3 %) were comfortable using video for patients who are not clinically stable. After the pandemic, most respondents (N = 422, 70.1 %) preferred to return to in-person care for the majority of visits; however, 95.3 % thought telemedicine should be offered in some form. Most (N = 481, 79.9 %) would continue to offer telemedicine if reimbursement were the same as in-person, while 242 (40.2 %) would continue if reimbursement were 25 % lower. Clinicians with more OUD patients used more telemedicine and reported higher comfort levels treating clinically unstable patients, and clinicians with more Medicaid/uninsured patients used more audio-only and preferred to continue using telemedicine post-pandemic. Conclusions: Telemedicine made up the majority of OUD visits provided by surveyed clinicians, and the vast majority of clinicians would like the option to offer telemedicine to at least some of their patients in the future if there is adequate reimbursement. These findings can help inform telemedicine's future role in the treatment of OUD.